Neuroscience‐informed computer‐assisted cognitive training in schizophrenia. Issue 1 (February 2016) - Fisher, Melissa; Herman, Alexander; Stephens, Dustin B.; Vinogradov, Sophia
Abstract : Schizophrenia is a heterogeneous psychiatric syndrome characterized by psychosis. It is also a neurodevelopmental disorder. In the earliest phases of the illness, at‐risk individuals exhibit subtle, nonspecific symptoms, including cognitive dysfunction and progressive brain volumetric loss. Generally, schizophrenia is characterized by abnormal/inefficient neural system operations and neural oscillatory activity, as well as functional disconnectivity across frontal–temporo parietal and frontal–subcortical networks; it thus may best be described as a widespread neural oscillatory connectomopathy. Despite earlier views of schizophrenia as an inevitably progressive neurodegenerative disease, emerging evidence indicates that endogenous neuroplastic capacity is retained. An active area of research is directed at understanding how best to harness this learning‐induced neuroplasticity to enhance neural system functioning, improve cognition, and prevent—and possibly even reverse—disease progression. In this review, we present an overview of results from the most widely used computer‐assisted cognitive‐training programs in schizophrenia, contrasting a broad neuropsychological rehabilitation approach with a targeted cognitive‐training approach. We then review studies on the neurobiological effects of these two training methods. Finally, we discuss future directions with a focus on the "oscillatory connectome" as a key area of investigation for developing the most precise and scientifically informed treatment approaches for this illness.